To solve the system of equations, we can use the method of substitution.
First, let's solve the second equation for y:
-6x + y = 32
y = 6x + 32
Now we can substitute this expression for y into the first equation:
4x - 8y = -36
4x - 8(6x + 32) = -36
4x - 48x - 256 = -36
-44x - 256 = -36
-44x = 220
x = -220/44
x = -5
We can substitute this value of x into the second equation to solve for y:
-6(-5) + y = 32
30 + y = 32
y = 32 - 30
y = 2
Therefore, the solution to the system of equations is x = -5 and y = 2.
Solve the system of equations
4x - 8y = -36
-6x + y = 32
1 answer